A Review on Possible Approaches for Detecting Early Warning Signs in Projects. Issue 5 (27th August 2013) - Haji‐Kazemi, Sara; Andersen, Bjørn; Krane, Hans Petter
Abstract In this paper, we attempt to provide an overview of the full extent of early warning detection approaches, which are directly or indirectly addressed in the literature. These approaches can aid project managers in taking corrective actions timely enough for preventing failures. The study is based on a review of the current literature within the field of early warning in project management and our own experiences gained from practice. An analysis of the strengths and weaknesses of each approach and their applications in different contexts are also performed. We conclude that the choice of the most effective approach is arguably dependent on the type of project, organizational culture, and the project environment.